Śrī Pañjeyavara nenapigāgi - Mangesha Rao, Panje; Govinda Pai, Manjeshwar, 1883-1963; Sitaramiah, Venkataramiah, 1899-; Karanth, Kota Shivarama, 1902- (SAMP early 20th-century Indian books project, 1952)
Festschrift honoring Panje Mageha Rao, Kannada author; comprises contributed articles on his life and works.